Growth and division of spiroplasmas: morphology of Spiroplasma citri during growth in liquid medium. - Garnier, M (1981)
The helical mycoplasma Spiroplasma citri was examined by electron microscopy with a newly developed transfer technique which preserves the helical morphology of the organism. The smallest viable cell was found to be a two-turn (elementary) helix. During the logarithmic phase of growth, organisms increased in length and divided by constriction, liberating two-turn elementary helices. The most frequently dividing parental helix was one with approximately four turns, yielding two elementary helices. Influence of pH and temperature on the morphology of the organism was also investigated. In unbuffered medium, growth of the organism produced a significant decrease in pH and a consequent formation of abnormal morphological forms and cell lysis. At 37 degrees C, cell division was inhibited, leading to a progressive disappearance of two-turn helices and an increase in the average length of other helices. Finally, helices were never seen to arise from round bodies at any stage of the growth cycle.